163 Brain Tissue Oxygenation and 3- and 6-month Neurological Outcome in Severe Traumatic Brain Injury. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Panczykowski, David Michael; Puccio, Ava; Chang, Yue-Fang; Shutter, Lori Anne; Okonkwo, David O.
Abstract: INTRODUCTION: Brain tissue oxygenation (PbtO2) monitoring has been utilized in the severe traumatic brain injury (sTBI) population as an in vivo tool to detect oxygenation changes in the acute injury phase. It has been previously reported that the longer a patient experiences a PbtO2 of = 15 torr, the greater the likelihood of death. The purpose of this study is to assess PbtO2 values and its relationship to 3- and 6-month outcome in adult sTBI. METHODS: Under an approved Internal Review Board protocol, PbtO2 data were prospectively collected on sTBI patients (Glasgow Coma Scale [GCS] score <9) during the acute 5 days following injury. Intensive care unit management included intracranial pressure (ICP) management per Guidelines of sTBI Management; however, PbtO2 was not treated, just monitored. Glasgow Outcome Scale (GOS) score, a measurement of neurologic outcome, was assessed at 3- and 6-months from injury and dichotomized into poor (GOS 1-3) and favorable outcome (GOS 4-5). Statistical analyses were performed using a logistic regression model controlling for age and initial severity of injury. RESULTS: Two hundred fifty-eight adult, sTBI patients with 3- and 6-month outcome were included. The mean age was 38 ± 17 years, with 69% male and a median GCS of 6. Post-trauma day (PTD) 2 PbtO2 data was chosen for analysis to avoid insertional microtrauma and minimize variability of values seen within the first 24 hours of monitoring. Logistic regression resulted in cut-off values of minimum PbtO2 <16.03 and maximum PbtO2 >37.15 being significant for poor 3-month neurological outcome (odds ratio, [OR] 2.46; 95% confidence interval [CI], 1.29-4.68; P = .004; and OR, 2.71; 95% CI, 1.37-5.33; P = .006, respectively). There was no residual significance for 6-month neurological outcome at these same cutoffs; however, PTD2 PbtO2 values in combination for minimum <18.3 and maximum >37.2 were significant predictors of poor outcome (OR, 2.02; 95% CI, 1.11-3.67; P = .02). CONCLUSION: Monitoring of PbtO2 in the adult sTBI population may be predictive of 3-month neurological outcome and provide a target cohort for early rehabilitation efforts. Additional studies are needed to assess the effectiveness of treating PbtO2 values.